Evaluation of Satellite-based Rainfall Data in Flood Prediction - Wisnulingga, Bayu Krisna; Sujono, Joko; Jayadi, Rachmad (Universitas Muhammadiyah Yogyakarta, 2023)
Rainfall-runoff transformation is a solution to the difficulty of obtaining observed discharge data in flood prediction analysis. Rainfall-runoff transformation requires observed rainfall data with a high rate of accuracy spatially. However, observed rainfall data is also often not available. Satellite rainfall data is commonly used to replace observed rainfall data. However, the accuracy of satellite rainfall data still needs to be tested. This study applied rainfall-runoff transformation to the observed rainfall data and the PERSIANN, GPM, and GSMaP satellite rainfall data in the Opak Watershed using GAMA I SUH method, which were then compared with the observed hydrograph at the AWLR Kretek during the flood event that occurred in Yogyakarta Province due to Cyclone Cempaka to evaluate their accuracy. The results showed that the GPM data generated a hydrograph that is the closest to the observed hydrograph, both the shape and the peak of the hydrograph.